Cone-beam computed tomography in the diagnostics of odontogenic maxillary sinusitis (LLC "Endo Press", 2020)
The article analyses changes of maxillary sinus detected by cone-beam computed tomography (CBCT) in case of various dental pathologies as well as of errors made during different kinds of dental treatment (endodontic treatment with filling material extruded into the sinus, dental implants). CBCT combined with software permitted the detection of X-ray signs testifying odontogenic origin of revealed changes in 71 (77%) patients with maxillary sinusitis out of 148 (100%).